PERBANDINGAN SENSITIVITAS ANTIBIOTIK MINOSIKLIN DAN ERITROMISIN TERHADAP BAKTERI Propionibacterium acnes PENYEBAB ACNE VULGARIS - Syavira Adinda Widiastuti; Diani Sri Hidayati; Herlinawati; Fahriana Azmi (Yayasan Nusantara Hasana Berdikari, 2023)
Acne vulgaris is a common skin disease that people complain about. Acne vulgaris is generally caused by Propionibacterium acnes bacterial infection. Treatment of Acne vulgaris can use antibiotics such as Minocycline and Erythromycin. Long-term use of antibiotics can lead to an increase in the occurrence of resistance. Research objective to determine the difference in sensitivity of Minocycline and Erythromycin antibiotics to Propionibacterium acnes bacteria that cause Acne vulgaris. This study used a type of laboratory pre-experimental research with a one-shot case study design. The research was conducted at the Health Laboratory Testing and Calibration Center (BLKPK) of NTB Province in February 2023. The sample used was Propionibacterium acnes bacteria. The data obtained were analyzed with the Independent t-test test. The results of Propionibacterium acnes bacteria are sensitive to Minocycline antibiotics with an average inhibition zone diameter of 22.8 mm and Erythromycin with an average inhibition zone diameter of 24.2 mm. Independent t-test results obtained a p-value of 0,688 which states there is no significant difference between the sensitivity of P. acnes bacteria to Minocycline and Erythromycin antibiotics. There is no difference in the sensitivity of Minocycline and Erythromycin antibiotics to Propionibacterium acnes bacteria that cause Acne vulgaris.